Coherency strain reduction in particles on a substrate as a driving force for solute segregation. (September 2016) - Amram, Dor; Barlam, David; Rabkin, Eugen; Shneck, Roni Z.
Abstract: It is well-established that solute segregation to interfaces is driven by the reduction of their energy. Here we propose coherency strain energy reduction due to lattice misfit modification at an interphase boundary, as a distinct driving force for segregation. Our experiments with Fe-Au particles on a sapphire substrate, together with finite element method calculations demonstrated that the elastic energy contribution to the total driving force for Au segregation exceeds its interfacial energy counterpart for particles larger than ~ 10 nm in size. Graphical abstract: